Modelo steam para la creatividad en estudiantes del primer año de la escuela general básica “Mercedes Amelia Guerrero” durante el año lectivo 2021-2022 - Rodríguez Angamarca, Yadira Del Rocío (2023)
ABSTRACT: The new education bases its processes on the capacities developed in the first years of basic education; it is in this period that competencies and skills that will serve children in later learning are promoted. In this context and considering that in the EGB Mercedes Amelia Guerrero of the Chambo canton, the classroom processes are faced with a disadvantage of educational resources, an investigation was carried out to determine how the STEAM model influenced the teaching-learning process and the development of creativity. For this purpose, we worked with a qualitative approach, with an ethnographic design, descriptive, field and transversal research, with a deductive scientific method. The research was carried out with thirty first year EGB students, to whom direct observation was applied to record data on their creativity levels, and twenty-one teachers, to whom a survey was conducted to evaluate their knowledge in the use of the STEAM system and the achievements obtained. The results reported indicate that this learning system has a positive influence on children's learning and makes possible a constructive approach by teachers to the application of activities oriented to the development of creativity as an integrating center in classroom processes. The results obtained allowed generalizations to be made, concluding that the STEAM system is a valuable tool for developing creativity and promoting meaningful learning. It was carried out as a proposal systematizing activities under the analyzed methodology that contribute to improve teachers' capabilities. Keywords: Classroom Processes, Teaching Learning, STEAM System, Creativity.